2016
DOI: 10.3390/brainsci6030038
|View full text |Cite
|
Sign up to set email alerts
|

Deep Brain Stimulation in Huntington’s Disease—Preliminary Evidence on Pathophysiology, Efficacy and Safety

Abstract: Huntington’s disease (HD) is one of the most disabling degenerative movement disorders, as it not only affects the motor system but also leads to cognitive disabilities and psychiatric symptoms. Deep brain stimulation (DBS) of the pallidum is a promising symptomatic treatment targeting the core motor symptom: chorea. This article gives an overview of preliminary evidence on pathophysiology, safety and efficacy of DBS in HD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 84 publications
0
32
0
1
Order By: Relevance
“…On the other hand, DBS of the GPe, although not currently used in clinical practice, has been indicated as a potential target for treatment given that it reduces discharge rate and bursting in GPi and STN in MPTP‐treated monkeys . Moreover, a PET study on patients with Huntington's disease revealed that bilateral GPe‐DBS modulated connectivity within the basal ganglia/thalamo‐cortical circuits and sensorimotor and default mode networks, promoting integration across these networks and therefore suggesting its potential role as a therapeutic target …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, DBS of the GPe, although not currently used in clinical practice, has been indicated as a potential target for treatment given that it reduces discharge rate and bursting in GPi and STN in MPTP‐treated monkeys . Moreover, a PET study on patients with Huntington's disease revealed that bilateral GPe‐DBS modulated connectivity within the basal ganglia/thalamo‐cortical circuits and sensorimotor and default mode networks, promoting integration across these networks and therefore suggesting its potential role as a therapeutic target …”
Section: Discussionmentioning
confidence: 99%
“…77 Moreover, a PET study on patients with Huntington's disease revealed that bilateral GPe-DBS modulated connectivity within the basal ganglia/thalamocortical circuits and sensorimotor and default mode networks, promoting integration across these networks and therefore suggesting its potential role as a therapeutic target. [78][79][80] In this framework, segmentation of the GP, based on multimodal structural and functional imaging in the setting of DBS, could improve patient outcome minimizing side effects. For example, Middlebrooks and colleagues showed that when a DBS electrode is located within the GP sensorimotor territory, the increase of volume tissue activated in the sensorimotor territory is correlated with improvement in the UPDRS.…”
Section: Pathophysiological Implications In Movement Disordersmentioning
confidence: 99%
“…DBS of the fornix (Lozano et al , ; Fig A) and the nucleus basalis of Meynert (Hardenacke et al , ) is being explored as a treatment for Alzheimer's. Combined stimulation of GPi and GPe (Fig B) is currently being explored for treating Huntington's disease to reduce the amount of choreatic movements and cognitive decline (Wojtecki et al , ).…”
Section: Current and Future Developmentsmentioning
confidence: 99%
“…DBS of the fornix ; Fig 7A) and the nucleus basalis of Meynert (Hardenacke et al, 2013) is being explored as a treatment for Alzheimer's. Combined stimulation of GPi and GPe ( Fig 7B) is currently being explored for treating Huntington's disease to reduce the amount of choreatic movements and cognitive decline (Wojtecki et al, 2016). As the traditional indication for DBS therapy, movement disorders continually see new developments to improve effectiveness or efficiency.…”
Section: Dbs Targets In Coronal Viewmentioning
confidence: 99%
“…Bei tardiven Syndromen und Stimulation des GPi oder des STN zeigten sich in einem Review von 117 Patienten Verbesserungen um mehr als 50 % [17]. Für die Chorea bei Morbus Huntington gibt es erste positive Ergebnisse bei der Stimulation des GPi [18].…”
Section: Merkeunclassified